Corynebacterium pacaense sp. nov., Alistipes megaguti sp. nov., Alistipes provencensis sp. nov., 3 new bacteria isolated from fresh human stool specimens - Bellali, S. (New Microbes New Infect, 2019)
Here we describe the basic characteristics of Corynebacterium pacaense strain Marseille-P2417(T) (= CSUR P2417), Alistipes megaguti strain Marseille-P5997(T) (= CSUR P5997) and Alistipes provencensis strain Marseille-P2431(T) (= CSUR P2431 = DSM 102308). The phenotypic criteria, the 16S ribosomal RNA sequencing and MALDI-TOF MS spectra analysis were used to identify and characterize these new bacteria species, which were isolated from fresh human stool specimens.